Does corporate social responsibility (CSR) have spillover effect? Based on the binary relationship of supply chains in China - Shanyun Qiu; Qian Liu; Weiting Luo; Jun Bai (China Journal of Accounting Studies (CJAS), 2023)
With data sampled from listed suppliers and customers in China from 2010 to 2017, the presenting work investigates how corporate social responsibility (CSR) is realised from the perspective of supply chains. Results found that socially responsible customers improved CSR performance of suppliers, revealing a significant CSR spillover effect among supply chains and further suggesting customers' bargaining power as an important realisation path. In addition, both the CSR sensitivity of customers and the CSR fulfilment ability of suppliers strengthened CSR spillover effect in supply chains. More importantly, suppliers' CSR performance is positive feedback to customers' need rather than a publicity stunt to cater to custo-mers. This paper expands current understanding on corporate behavioural coordination from the perspective of supply chains and provides insights for promoting CSR fulfilment in the Chinese scenario.
Keywords: 650; Corporate social responsibility; supply chains; spillover effect; bargaining power